Initial Reports of the Deep Sea Drilling Project 1984
DOI: 10.2973/dsdp.proc.74.122.1984
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial Water Studies, Leg 74

Abstract: Interstitial water studies from sites drilled during a transect of the Walvis Ridge indicate that concentration increases in calcium and decreases in magnesium toward and into the basement. These trends can be understood principally in terms of reactions taking place in Layer 2 of the oceanic crust. At Site 525, however, some removal of magnesium occurs within the sediment column. Concentration maxima of dissolved strontium clearly indicate that carbonate recrystallization occurs throughout the carbonate sedim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1984
1984
2020
2020

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…At this site, we noted nitrate enrichment in the crustal fluids at the sediment/basement interface relative to background seawater. In line with its representation, this geochemical signal has been detected in the few studied locations characterized by vigorous low-temperature hydrothermal circulation (e.g., the East Pacific Rise [44] and the Clarion-Clipperton Fracture Zone [45]). Such nitrate enrichment in the crust may result from (i) high-level downward nitrate flux from the overlying sediments (25) or (ii) a downward flux combined with in situ nitrification.…”
Section: Discussionsupporting
confidence: 62%
“…At this site, we noted nitrate enrichment in the crustal fluids at the sediment/basement interface relative to background seawater. In line with its representation, this geochemical signal has been detected in the few studied locations characterized by vigorous low-temperature hydrothermal circulation (e.g., the East Pacific Rise [44] and the Clarion-Clipperton Fracture Zone [45]). Such nitrate enrichment in the crust may result from (i) high-level downward nitrate flux from the overlying sediments (25) or (ii) a downward flux combined with in situ nitrification.…”
Section: Discussionsupporting
confidence: 62%
“…At Sites 699, 700, and 702, the downhole gradients in Ca and Mg are linear with depth and reflect diffusional gradients between the overlying seawater and basalt-seawater reactions occurring in basement (McDuff, 1981;Gieskes, 1983;Gieskes et al, 1984). The calcium vs. magnesium relationship at these three sites is linear with a ΔMg/ΔCa slope of -0.5 ( Fig.…”
Section: Basalt Basement Reactions Vs Silicic Volcanic Ashmentioning
confidence: 89%
“…Studies of interstitial waters from accretionary convergent plate margins revealed the importance of element transfer by fluid flow in accretionary wedges. These studies include those during n DSDP Legs 66 and 67 (Harrison et al, 1982;Gieskes et al, 1985) and Leg 84 (Hesse et al, 1985) in the Middle America Trench, during ODP Leg 110 on the Barbados Ridge (Shipboard Scientific Party, 1988a), and during ODP Leg 112 at the Peru continental margin (Shipboard Scientific Party, 1988b). The principal characteristics of these forearc fluids are low chlorinities and the presence of hydrocarbons, especially methane, which form gas hydrates, given appropriate temperatures, pressures, and partial pressure of the hydrocarbons.…”
Section: Chemical Fluxes In Forearc Terranesmentioning
confidence: 99%